2016
DOI: 10.1063/1.4945622
|View full text |Cite
|
Sign up to set email alerts
|

The origin of unequal bond lengths in the C̃1B2 state of SO2: Signatures of high-lying potential energy surface crossings in the low-lying vibrational structure

Abstract: The C̃ (1)B2 state of SO2 has a double-minimum potential in the antisymmetric stretch coordinate, such that the minimum energy geometry has nonequivalent SO bond lengths. The asymmetry in the potential energy surface is expressed as a staggering in the energy levels of the ν3(') progression. We have recently made the first observation of low-lying levels with odd quanta of v3('), which allows us-in the current work-to characterize the origins of the level staggering. Our work demonstrates the usefulness of low… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In the observed vibrational origins given in Tables VII and VIII (and pictured in Fig. 1 of the third part of this series 11 ) it is evident that levels with a single quantum of ν 3 are significantly depressed in frequency. However, the degree of odd-even staggering rapidly decreases with increasing v 3 , indicating a low barrier at the C 2v geometry.…”
Section: Vibrational Level Structurementioning
confidence: 81%
See 3 more Smart Citations
“…In the observed vibrational origins given in Tables VII and VIII (and pictured in Fig. 1 of the third part of this series 11 ) it is evident that levels with a single quantum of ν 3 are significantly depressed in frequency. However, the degree of odd-even staggering rapidly decreases with increasing v 3 , indicating a low barrier at the C 2v geometry.…”
Section: Vibrational Level Structurementioning
confidence: 81%
“…The observation of b 2 vibrational levels allows us to determine much more accurate rotational constants for both the b 2 and a 1 vibrational levels, because it enables direct deperturbation of the strong Coriolis interactions. In Part II of this series, 9 we describe an internal force field determination of the potential energy surface for the C state around equilibrium, and in Part III 11 we model the vibronic mechanism for the observed staggered vibrational level structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the former, experimental evidence has been provided that the C ̃B2 1 state has a double minimum along the antisymmetric stretching vibrational mode, leading to unequal bond lengths, i.e., to a C s , rather than C 2v , structure as a minimum. 39 For the A ̃B2 2 state of SO 2 + , Chang et al found analogous behavior theoretically by carrying out vibrational frequency calculations for this state with densityfunctional theory (DFT) and complete active space selfconsistent field (CASSCF) methods. 30 Are these theoretical approaches reliable enough for describing such a subtle, doubleminimum situation?…”
Section: ■ Introductionmentioning
confidence: 97%